Increase in production capacity in chemical plants, with no investment in new assets - Lana, João Batista de; Marins, Fernando Augusto Silva; Muniz Junior, Jorge (Revista Gestão da Produção Operações e Sistemas, 2008)
This paper presents the procedure used to increase the production capacity of a Chemical Industry locatedat São Paulo State, without new assets investment, which applies Continuous Process Improvement concepts,including Theory of Constraints (TOC) and Value Based Management (VBM). The obtained results, carriedout by a team with multidiscipline skills, has been positive to the Company, with highlight, among the tangibleresults to an increasing of 20% in production capacity and among the intangible ones, to a better Demand andProduction Planning Management Process that was implemented. Finally, suggestions and recommendationsto similar applications to be well succeeded are presented.Keywords: Capacity, Theory of constraints, Value based management, Production bottleneck, Continuous improvement.